Psoriasis, Cardiovascular Events, and Biologics: Lights and Shadows - Caiazzo, Giuseppina; Fabbrocini, Gabriella; Di Caprio, Roberta; Raimondo, Annunziata; Scala, Emanuele; Balato, Nicola; Balato, Anna (Frontiers in Immunology, 2018)
Nowadays, it is well established a link between psoriasis and cardiovascular (CV) diseases. A series of different overlapping mechanisms including inflammation, homeostasis dysregulation, and genetic susceptibility are thought to underlie this association. Advances in understanding the molecular patterns involved in the complex scenario of psoriasis have highlighted a tight correlation with atherosclerosis. Indeed, common profiles are shared in term of inflammatory cytokines and cell types. In the last decade, the management of psoriasis patients has been revolutionized with the introduction of biological therapies, such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-12/23, and IL-17 inhibitors. In clinical setting, the effectiveness of these therapies as well as the incidence of CV events is related to the type of biologics. In particular, anti-TNF-α agents seem to reduce these events in psoriasis patients whereas anti-IL-12/23 agents related CV events reduction still remain to clarify. It has to be taken into account that IL-12/23 inhibitors have a shorter post-marketing surveillance period. An even more restricted observational time is available for anti-IL-17 agents. IL-17 is associated with psoriasis, vascular disease, and inflammation. However, IL-17 role in atherosclerosis is still debated, exerting both pro-atherogenic and anti-atherogenic effects depending on the specific context. In this review, we will discuss the differences between the onset of CV events in psoriasis patients, referred to specific biological therapy and the underlying immunological mechanism. Given the development of new therapeutic strategies, the investigation of these inhibitors impact on heart failure outcome is extremely important.